Prevalencia de Leptospira spp. en perros de la parroquia de Calderón, Manabí, Ecuador - Bravo Caicedo, Nohelia Anahís (2025)
The study consisted of determining the prevalence of Leptospira spp. in dogs in Calderón parish, Manabí, Ecuador, for this purpose seventy-eight blood samples were collected from dogs from 31 farms, selected by simple random convenience sampling. Prevalence was determined by examination of blood samples analyzed at the laboratory of the Instituto Nacional de Investigación en Salud Pública del Ecuador Leopoldo Izquieta Pérez - INSPI LIP with the LightCycler® 480 PCR system. The results obtained indicated the absence of positive cases in the samples of the dogs evaluated, which evidenced that there is no prevalence of Leptospira spp. Descriptive statistics were used to analyze the data using the Excel program version 2016. Although no prevalence of the disease was detected, it was inheriting the need to discern the existence of risk factors that were associated with the presentation of the pathology, among them, the study identified possible conditions that in the future could favor the appearance of the disease; the order of relevance was the following: habitat (dogs living outside the house), dogs not vaccinated against Leptospira spp, lack of rat extermination in homes and abortions. The dogs evaluated on the farms are currently considered free of Leptospirosis, which is a positive indicator in terms of public health. However, active epidemiological surveillance should be maintained to identify the presence of Leptospira spp. in a timely manner and to develop preventive strategies to mitigate the risk of transmission of this zoonosis in the region.